2009
DOI: 10.2165/00002018-200932050-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia with Oral Antidiabetic Drugs

Abstract: This analysis shows that the frequency of reported hypoglycaemia within the study cohorts was relatively low. The rates of hypoglycaemia were not equal between drug classes. Treatment with nateglinide or repaglinide was characterized by a higher incidence of hypoglycaemia at the beginning of treatment. Further investigation is necessary to assess whether women treated with TZDs are more prone to hypoglycaemia than men. Findings from this study should be taken into account with other clinical and pharmacoepidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…When we examined the use of TZD in conjunction with sulfonylureas and insulin (two of the most commonly used medications in ACCORD), we found the highest rates of hypoglycemia among those who were prescribed TZDs in combination with insulin as compared to the combination of TZD with sulfonylureas. Among those participants who were prescribed TZD but not sulfonylurea or insulin, the incidence rate of severe hypoglycemia was similar to that reported in a prescription monitoring program [16]. Although the mechanism for this finding is not clear, it is possible that the insulin sensitizing action of the TZD accentuates the risk of hypoglycemia of insulin when these two are used in combination.…”
Section: Discussionsupporting
confidence: 69%
“…When we examined the use of TZD in conjunction with sulfonylureas and insulin (two of the most commonly used medications in ACCORD), we found the highest rates of hypoglycemia among those who were prescribed TZDs in combination with insulin as compared to the combination of TZD with sulfonylureas. Among those participants who were prescribed TZD but not sulfonylurea or insulin, the incidence rate of severe hypoglycemia was similar to that reported in a prescription monitoring program [16]. Although the mechanism for this finding is not clear, it is possible that the insulin sensitizing action of the TZD accentuates the risk of hypoglycemia of insulin when these two are used in combination.…”
Section: Discussionsupporting
confidence: 69%
“…The preferred drugs in MetS are those that do not have a direct effect on pancreatic β-cells, such as biguanides (metformin), thiazolidinediones (rosiglitazone), and α-glucosidase inhibitors (acarbose) (Mamedov and Shishkova, 2007 ). The main advantage of these euglycemic agents is avoiding hypoglycemia as a side effect (Vlckova et al, 2009 ).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…A recent observational study from the U.K. studying the incidence of hypoglycemia in patients using different oral anti-diabetic drugs concluded that the incidence rate of hypoglycemia was 50%–100% less in pioglitazone treated patients as opposed to those who were on nateglinide or repaglinide 23. An interesting observation was that hypoglycemia was more common in women on TZDs (pioglitazone and rosiglitazone) than men on similar drugs 23. Pioglitazone monotherapy was associated with much less hypoglycemia than glyburide treated patients with newly diagnosed type 2 diabetes (24.3% in glyburide group vs. 4.4% in pioglitazone group, P = 0.0001) 24.…”
Section: Introductionmentioning
confidence: 99%